Effect of Aluminum Powder additive on Erosion and Bending Resistance of Galvanize Layer - kamil Othman, Abbas; ., .; ., . (International Journal of Engineering and Technology, 2018)
Study of the effect of adding aluminum powder to galvanize melt on the microstructure, thickness of the galvanize layer, behavior and nature of fracture in the total layer through the use of optical microscope and scanning electron microscopy. The addition of the aluminum component (4.5%, 5%, 5.5%) to molten is increase the totalÂ thickness of the galvanize layer because it increases the thickness of the interlayer and the adhesive layer with the low carbon steel coupled with the increased dipping time in the molten which also increases the thickness of the total galvanize layer. The cracks that were obtained from the bending test were examined for the samples. The samples with the large thickness and the addition ratio (Al-5.5%) were more resistant to bending. The cracks did not penetrate the surface of the galvanize layer until the angle of bending with the horizon (30Âº). The erosion resistance was compared to the exposure time of the selection samples, and showed good resistance to erosion at average exposure time. These samples are good in the manufacture of high and medium voltage transmission towers. Â